Systemic mutational analysis of the TGFβ signalling pathway in thoracic aortic aneurysms and dissections. (12th October 2011) - Wang, Wen-Jing; Zheng, Jun; Hu, Fang-Yuan; Zhu, Yun; Xie, Jin-Sheng; Guo, Jian; Zhang, Zhe; Dong, Jie; Zheng, Gu-Yan; Cao, Huiqing; Liu, Tian-Shu; Han, Peili; et al.
Abstract : Purpose: Excessive activation of the TGFβ signalling pathway caused by genetic mutations is known to be responsible for the inherited thoracic aortic aneurysms and dissections (TAAD) that is life-threatening and characterised by a broad spectrum of connective tissue disorders. This study was designed to figure out: (1) whether other components in the TGFβ signalling pathway contribute to TAAD and (2) whether mutations in the TGFβ signalling pathway account for the majority of TAAD sufferers. Methods: We performed mutational screening in the critical components associated with the TGFβ signalling pathway and its target genes, including TGFB1, TGFBR1, TGFBR2, SMAD2, SMAD3, SMAD4, SMAD6, SMAD7, FBN1, BGN, EFEMP2, TAGLN and ACTA2 genes in 21 sporadic TAAD participants and 8 affected families from Han Chinese. Additionally we reviewed all mutational studies of FBN1 and identified several features in the correlation between genotypes and clinical manifestations in Chinese patients compared with other ethnic groups. Results: Of 29 identified sequence variants, 23 were potential mutations in FBN1, TGFBR2, SMAD2 and SMAD3 as were not found in 500 healthy individuals, accounting for 80% of TAAD patients. Six appeared novel SNPs in FBN1, SMAD3 and SMAD7. We demonstrated that c.5917+6T>C caused skipping of exon 47, leading to the loss of the 29th cbEGF-like domain associated with Marfan syndrome without ectopia lentis. Conclusions: Our study indicates that genetic alteration of TGFβ signalling pathway is a major cause for the inherited form of TAAD despite of ethnic effects.